Incidental Detection of Internal Jugular Vein Thrombosis Secondary to Undiagnosed Benign Substernal Goiter - Mai Tone Lønnebakken; Ole Martin Pedersen; Knut Sverre Andersen; Jan Erik Varhaug (Case Reports in Medicine)
Internal jugular vein thrombosis is a serious event with potentially fatal outcome, where the clinical symptoms may be vague or absent. This paper refers to a rare case where routine carotid Doppler ultrasound prior to coronary artery bypass grafting (CABG) and aortic valve replacement (AVR) in a 76-year-old man, incidentally revealed thrombosis of the right internal jugular vein. Thoracic CT demonstrated an underlying, large, benign substernal multinodular goiter, mainly involving the right lobe, causing compression and displacement of the great vessels. A successful, one-stage operation including ligation of the internal jugular vein to avoid pulmonary embolism and hemithyroidectomy, combined with the scheduled CABG and AVR, was performed. This case illustrates that benign substernal goiter may be associated with asymptomatic internal jugular vein thrombosis. Carotid Doppler ultrasound should involve evaluation of the internal jugular vein concerning thrombosis as its presence may reveal space-occupying lesions in the thorax.